Characteristics and atmospheric drivers of large‐scale agrometeorologically relevant dry spells in sub‐seasonal to seasonal timescales over Zimbabwe - Gibbon I. T. Masukwedza; Victoria L. Boult; Melissa Lazenby; Martin C. Todd (Meteorological Applications)
Abstract This article pioneers a unique approach to examining generic dry spells, shifting focus from traditional rain‐free period analysis to a crop‐centric perspective that integrates an anticipatory lens inspired by Impact‐based Forecasting (IbF). Moving beyond traditional analyses of rain‐free periods, the article evaluates these impactful within‐season large‐scale agrometeorologically relevant dry spells (LARDS) not by the number of days with minimal or no rainfall but by their impact—specifically, the adequacy of root‐zone soil moisture to meet the optimal requirements of maize crops, as quantified through the Water Requirement Satisfaction Index (WRSI). LARDS were identified in maize‐intensive growing regions of Zimbabwe under two maize planting date scenarios: meteorology‐guided and uninformed. The research characterizes impactful within‐season LARDS occurring at sub‐seasonal to seasonal timescales over 36 years (1983–2018). Findings show that meteorological guidance improves yields while neglecting it results in lower yields. During LARDS, a distinct northwest‐to‐southeast suppressed rainfall pattern emerges over Zimbabwe, extending into neighbouring countries. This pattern is associated with a southwestward or northeastward displacement of Tropical Temperate Troughs (the regional primary rainfall system) relative to the country's location. Furthermore, LARDS exhibit overarching anticyclonic conditions impeding vertical cloud development with notable changes in the key local large‐scale mean climatic features influencing Southern Africa's weather. Specifically, the Mozambique Channel Trough, Angola Tropical Low, Saint Helena High and Mascarene High weaken anomalously, while the Botswana High strengthens during LARDS. Additionally, we demonstrate that LARDS have a northeastward propagation and have atmospheric signatures indicative of being triggered by upstream Rossby waves originating from the south coast of South America.